DEVELOPMENT OF A MODIFIED PAPERFUGE FOR FIELD DIAGNOSIS OF ANEMIA IN CEBU, PHILIPPINES - Amodia, Jose Moses A.; Ybañez, Adrian P.; Chico, James Knowell E.; Ybañez, Rochelle Haidee D.; Moumouni, Paul Franck Adjou C.; Xuan, Xuenan (Journal of Agriculture and Technology Management; Journal of Agriculture and Technology Management (JATM) Volume 20 Issue 2, July-December 2017, 2018)
The packed cell volume (PCV) or hematocrit can be used as an indicator of an animal’s health status. An animal with a low PCV value will usually have an anemia, which may be caused by tick-borne pathogens. PCV is routinely measured by equipment which can be expensive and difficult to bring in the field. Thus, developing an alternative method or tool that can be applied in the field to determine PCV would be advantageous. The present study aimed to develop a modified paperfuge, assess its reliability in different animals and evaluate its relevance to the diagnosis of Mycoplasma spp. infection in cattle and water buffalo. Initially, a modified paperfuge tool using locally available materials and its corresponding technique for usage was developed. Its reliability was assessed in different animal species (dog, cat, sheep, cattle, goat) along with other equipment, including an automated hematology analyzer and standard centrifuge. Results showed that the red blood cell count (RBC) was associated with PCV. Further statistical analyses showed that except in cats, there were highly significant correlations between the improvised paperfuge method and the other established methods. Field application of the modified paperfuge was performed in 12 water buffaloes and 40 cattle, which were tested for Mycoplasma spp. infection using polymerase chain reaction (PCR). Molecular detection for the presence of Mycoplasma spp. showed no correlation between the PCV values obtained. This study supports the reliability of the paperfugation technique and showed its applicability in field conditions. However, as results showed that PCV cannot be used as an indicator of the infection, paperfuge cannot be reliably used to diagnose hemoplasma infection, most especially in asymptomatic cases.